Benign Nocturnal Alternating Hemiplegia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
Two brothers who developed recurrent attacks of alternating hemiplegia arising out of sleep, distinguishable from classical alternating hemiplegia of childhood (AHC), are reported from Montreal Neurological and Children's Hospitals, and Children's Hospital of Western Ontario, London, ON, Canada.